The most Effective Speaking Classroom Activities at University of Constantine - HADEF, Rima (Journal of Human Sciences, 2016)
Speaking is one of the language skills to be developed in learning foreign languages. It is defined as the delivery of language via sounds and words and it is the key of oral communication. The literature has often cited difficulties in learning how to speak a foreign language fluently and accurately. Learning how to communicate needs intensive practice which is considered the main obstacle for learners since it requires appropriate conditions such as very small groups of students and enough time which is not the case at university of Constantine. Since adding extra hours for this module and decreasing the number of students per group seem to be beyond the realm of possibility, searching for new ways to improve communication is the right solution. The purpose of this paper then is to provide both teachers and learners of English with the most effective activities which can work with the prevailing conditions that are likely to enhance learners’ proficiency in speaking.